Thrombosis in the Surgically Corrected Anomalous Right Coronary Artery after Reimplantation in Aorta. (31st December 2017) - Bajwa, Ata; Gupta, Bhanu; Ya'qoub, Lina; Laster, Steven B.; Thompson, Randall
Abstract : A 32-year-old African American female presented with dyspnea, and after several cardiac diagnostic tests, the diagnosis of an anomalous origin of the RCA from the pulmonary trunk was established by multislice coronary CT angiography. She underwent surgical correction with reimplantation of the RCA, from the pulmonary artery to the aortic root. However, 10 days after surgery, she developed frequent episodes of chest pain, and repeat coronary CTA showed a partially occlusive thrombus in the surgically reimplanted RCA. Anticoagulation with warfarin resulted in complete resolution of the patient's symptoms.